ANALYSIS OF EMPLOYEE PAYROLL INTERNAL CONTROL SYSTEM AT PT. ZIKRUL HAKIM BESTARI SURABAYA BRANCH - Dian Fahriani; Dinda Rahma Yanuari (Universitas Nahdlatul Ulama Sidoarjo, 2022)
This study aims to determine the payroll system and internal control of the payroll system at PT. Zikrul Hakim Bestari Surabaya Branch. This study uses a qualitative descriptive research method. Data were collected by interview and documentation methods. The results showed that the payroll system carried out by PT. Zikrul Hakim Bestari Surabaya Branch has gone through the system: AppSheet, Sisfo Audit and Payroll. The head office in Ciawi, Bogor, carries out payroll. The only function that is applied is the payroll function and the financial function; even then, it is carried out by the same person. Documents used in the payroll process are employee attendance lists and salary slips. Human errors occur in the company's payroll process (data entry errors). Internal control of payroll at PT. Zikrul Hakim Bestari Surabaya Branch has done well, although not optimally. This can be seen from the dual tasks that occur in the company.